(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The importance of reflection on the role that environmental protection is assuming within the constitutional landscape is emerging with increasing urgency. Starting from the constitutional revision of Articles 9 and 41 and an analysis of the idea of the environment to be protected, one finds oneself faced with a principle that impacts the Constitution in several respects. In fact, relating the principle of environmental protection to the provisions of Article 2 gives rise to a duty of environmental solidarity in the hands of all the subjects of the Republic, both public and private, which unfolds in both intragenerational and intergenerational directions and which modifies certain characteristics of the category of subjective right. Moreover, one must highlight the repercussions that this formal constitutionalising may have on the balancing of constitutional values, with reference to the freedom of economic initiative.